2014
DOI: 10.1177/1468796813518314
|View full text |Cite
|
Sign up to set email alerts
|

The role of different forms of bridging capital for immigrant adaptation and upward mobility. The case of Ukrainian and Vietnamese immigrants settled in Poland

Abstract: This paper analyses the adaptation strategies of Vietnamese and Ukrainian immigrants having permit for settlement in Poland and settled in Warsaw and its vicinity (namely in the Mazowieckie province), with an emphasis on the relationship between the cultural, social and economic dimensions of adaptation. The research showed that due to the large cultural distance between the Vietnamese and Polish societies as well as the specific socio-cultural characteristics of Vietnamese immigrants (e.g. strong ethnic ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
0
14
1
4
Order By: Relevance
“…Another focus of interest is forced migration, including refugees and issues of forced labor (Dąbrowski, 2014; Ząbek and Łodziński, 2008). The Vietnamese community remains relatively understudied, although some comparative research projects (Fihel, 2008; Grzymała-Kazłowska, 2014; Kindler and Szulecka, 2013) include Vietnamese immigrants. In studies comparing Vietnamese and Ukrainians, the former were found to be less assimilated to Poland due to greater cultural distance and fewer contacts with the host society (Grzymała-Kazłowska, 2014).…”
Section: Background and Contextmentioning
confidence: 99%
“…Another focus of interest is forced migration, including refugees and issues of forced labor (Dąbrowski, 2014; Ząbek and Łodziński, 2008). The Vietnamese community remains relatively understudied, although some comparative research projects (Fihel, 2008; Grzymała-Kazłowska, 2014; Kindler and Szulecka, 2013) include Vietnamese immigrants. In studies comparing Vietnamese and Ukrainians, the former were found to be less assimilated to Poland due to greater cultural distance and fewer contacts with the host society (Grzymała-Kazłowska, 2014).…”
Section: Background and Contextmentioning
confidence: 99%
“…Afrikalı göçmenlerin İstanbul' da zor şartlar altında yaşamasının diğer nedeni ise gündelik hayatta, işte, sokakta, toplu taşıma araçlarında, kurumlarda maruz kaldıkları ırkçılıktır (Şimşek, 2019). Göçmenler ve göç alan toplum bireyleri arasındaki ilişkiler göçmenlerin adaptasyonu ve sosyal uyum için önemli bir unsur olarak görülmektedir Dahinden, 2013;Grzymala-Kazlowska, 2015;Sturgis, Smith, Kuha & Jackson, 2013). Birçok araştırma, göçmenler ve göç alan toplum bireyleri arasında iletişimin ve dostluğun kurulduğu bir ortamda, göçmenlerin kendilerini güvende hissettiklerini ve entegrasyon sürecinin kolaylaştığını göstermektedir.…”
Section: İstanbul'daki̇ Afri̇kali Göçmenleri̇n Entegrasyon Süreçleri̇ Vunclassified
“…Bu nedenle entegrasyon, haklar ve yükümlülükler dengesi olarak algılanır ve entegrasyon politikaları ekonomik, sosyal ve politik haklar, kültürel ve dini çeşitlilik, vatandaşlık ve katılımı kapsayan bütünsel bir yaklaşım içerir. Entegrasyonun iki taraflı bir süreç olarak tanımlanması, göçmenler ve göç alan toplum bireyleri arasında kurulan sosyal ilişkilerin önemini de vurgulamaktadır (Ager & Strang, 2008;Grzymala-Kazlowska, 2015;Phillimore, 2012). Bununla birlikte, göçmenlerin entegrasyon süreçleri çeşitli göç nedenleri ve göçmen statülerine göre farklılık göstermektedir (Castles vd., 2002).…”
Section: Introductionunclassified
“…The Vietnamese have a highly expanded support network within their ethnic group and are perceived as economically, socially, and culturally isolated from Polish society (Halik 2006;Halik & Nowicka 2002). Research indicates that they have a strong ethnic identity, their family and social networks consist mainly of representatives of their own ethnic group members, and they tend to concentrate spatially with regard to accommodation (Grzymała-Kazłowska & Piekut, 2007;Grzymała-Kazłowska, Stefań ska & Szulecka, 2008;Górny et al, 2010;Grzymała-Kazłowska, 2015). On the other hand, the Vietnamese are active in forming ethnic organisations, and community leaders and activists make efforts to introduce Vietnamese culture to the majority Polish society, especially by means of educational and cultural projects (Szyman´ska-Matusiewicz, 2015b).…”
Section: Vietnamese Migrantsmentioning
confidence: 99%
“…On the other hand, the Vietnamese are active in forming ethnic organisations, and community leaders and activists make efforts to introduce Vietnamese culture to the majority Polish society, especially by means of educational and cultural projects (Szyman´ska-Matusiewicz, 2015b). This leads to the "collective integration" of the group as a whole into the host society (Grzymała-Kazłowska, 2015). It must also be stressed here that the Vietnamese in Poland are very diverse within their group; for instance, with regard to legal status (some are undocumented, short-term, or long-term migrants, whilst others have Polish citizenship); political views; language acquisition; economic status (some are low-skilled workers, whilst others run their own businesses and employ both Poles and foreigners); as well as standard of living (some rent apartments along with numerous other immigrants, whilst others own apartments in gated settlements) (see also Szyman´ska-Matusiewicz, 2015b).…”
Section: Vietnamese Migrantsmentioning
confidence: 99%